Mining Data from reservoir Simulation Results - Akmal , Aulia (2010)
In finding optimum settings in reaching the highest oil recovery of a given reservoir,many parameters are involve such as flow rates and bottomhole pressure.Therefore, petroleum engineers need to perform several trials and error process alongside engineering experiences in order to tune the right parameters. In this study, we randomly generate the values and perform simulation via ECLIPSE software in order to obtain oil recovery values.Several simulations lead to formation of data set which will be analyzed by well known data mining method,the Association RULES (ARULES. With ARULES we can see how several parameters can interact and contribute to either increase/decrease of oil recovery.